Evaluation of the performance of Iraqi university buildings according to the standards of leadership in energy and environmental design (Journal of Accounting and Financial Studies ( JAFS ), 2025)
In recent years, interest in sustainable buildings has increased, to conserve the resources consumed in building these buildings, and in order for the process of building designs and their use to be environmentally friendly, these buildings must be subject to evaluation systems that enhance resource and energy conservation and environmental safety, including the Leadership in Energy and Environmental Design (LEED) system. Where Al-Hikma College was evaluated according to the criteria of the Leadership in Energy and Environmental Design (LEED) system within the determinants of the system's criteria, namely (sustainable site, sustainable site and transportation, energy and atmosphere, materials, resources and waste management, indoor environmental quality) and through the evaluation of the building according to the determinants of the system's criteria and according to the evaluation levels of the LEED system criteria, the values ​​for the sustainable site were (4), sustainable site and transportation (14), energy and atmosphere (35), materials, resources and waste management (9), and indoor environmental quality (22). The final result of the standard value was (14.5), where the building is classified among the non-certified buildings according to the classification of the proposed system levels.